Ethical Considerations for Research Involving Prisoners - Institute of Medicine
In the past 30 years, the population of prisoners in the United States has expanded almost 5-fold, correctional facilities are increasingly overcrowded, and more of the country's disadvantaged populations&#8212racial minorities, women, people with mental illness, and people with communicable diseases such as HIV\/AIDS, hepatitis C, and tuberculosis&#8212are under correctional supervision. Because prisoners face restrictions on liberty and autonomy, have limited privacy, and often receive inadequate health care, they require specific protections when involved in research, particularly in today's correctional settings. Given these issues, the Department of Health and Human Services' Office for Human Research Protections commissioned the Institute of Medicine to review the ethical considerations regarding research involving prisoners. The resulting analysis contained in this book, Ethical Considerations for Research Involving Prisoners, emphasizes five broad actions to provide prisoners involved in research with critically important protections: &#8226 expand the definition of \

Ethical Conduct of Clinical Research Involving Children - Institute of Medicine (The National Academies Press, 2004)
In recent decades, advances in biomedical research have helped save or lengthen the lives of children around the world. With improved therapies, child and adolescent mortality rates have decreased significantly in the last half century. Despite these advances, pediatricians and others argue that children have not shared equally with adults in biomedical advances. Even though we want children to benefit from the dramatic and accelerating rate of progress in medical care that has been fueled by scientific research, we do not want to place children at risk of being harmed by participating in clinical studies. Ethical Conduct of Clinical Research Involving Children considers the necessities and challenges of this type of research and reviews the ethical and legal standards for conducting it. It also considers problems with the interpretation and application of these standards and conduct, concluding that while children should not be excluded from potentially beneficial clinical studies, some research that is ethically permissible for adults is not acceptable for children, who usually do not have the legal capacity or maturity to make informed decisions about research participation. The book looks at the need for appropriate pediatric expertise at all stages of the design, review, and conduct of a research project to effectively implement policies to protect children. It argues persuasively that a robust system for protecting human research participants in general is a necessary foundation for protecting child research participants in particular.

The State of Anti-Black Racism in the United States: Reflections and Solutions from the Roundtable on Black Men and Black Women in Science, Engineering, and Medicine: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
The mission of the Roundtable on Black Men and Black Women in Science, Engineering, and Medicine at the National Academies of Sciences, Engineering, and Medicine is to advance discussions on the barriers and opportunities encountered by Black students and professionals as they navigate the pathways from K-12 and postsecondary education to careers in science, engineering, and medicine (SEM) and highlight promising practices for increasing the representation, retention, and inclusiveness of Black men and Black women in SEM. This proceedings serves as a summary of the presentations and discussions from a capstone workshop, held virtually on December 6 and 7, 2021, to review how anti-Black racism had permeated across the topics covered by the Roundtable over the previous 2 years.

Environmental Decisions in the Face of Uncertainty - Institute of Medicine (The National Academies Press, 2013)
The U.S. Environmental Protection Agency (EPA) is one of several federal agencies responsible for protecting Americans against significant risks to human health and the environment. As part of that mission, EPA estimates the nature, magnitude, and likelihood of risks to human health and the environment; identifies the potential regulatory actions that will mitigate those risks and protect public health1 and the environment; and uses that information to decide on appropriate regulatory action. Uncertainties, both qualitative and quantitative, in the data and analyses on which these decisions are based enter into the process at each step. As a result, the informed identification and use of the uncertainties inherent in the process is an essential feature of environmental decision making. EPA requested that the Institute of Medicine (IOM) convene a committee to provide guidance to its decision makers and their partners in states and localities on approaches to managing risk in different contexts when uncertainty is present. It also sought guidance on how information on uncertainty should be presented to help risk managers make sound decisions and to increase transparency in its communications with the public about those decisions. Given that its charge is not limited to human health risk assessment and includes broad questions about managing risks and decision making, in this report the committee examines the analysis of uncertainty in those other areas in addition to human health risks. Environmental Decisions in the Face of Uncertainty explains the statement of task and summarizes the findings of the committee.

The Postdoctoral Experience Revisited - National Academy of Sciences; National Academy of Engineering; Institute of Medicine (The National Academies Press, 2014)
The Postdoctoral Experience Revisited builds on the 2000 report Enhancing the Postdoctoral Experience for Scientists and Engineers. That ground-breaking report assessed the postdoctoral experience and provided principles, action points, and recommendations to enhance that experience. Since the publication of the 2000 report, the postdoctoral landscape has changed considerably. The percentage of PhDs who pursue postdoctoral training is growing steadily and spreading from the biomedical and physical sciences to engineering and the social sciences. The average length of time spent in postdoctoral positions seems to be increasing. The Postdoctoral Experience Revisited reexamines postdoctoral programs in the United States, focusing on how postdocs are being guided and managed, how institutional practices have changed, and what happens to postdocs after they complete their programs. This book explores important changes that have occurred in postdoctoral practices and the research ecosystem and assesses how well current practices meet the needs of these fledgling scientists and engineers and of the research enterprise. The Postdoctoral Experience Revisited takes a fresh look at current postdoctoral fellows - how many there are, where they are working, in what fields, and for how many years. This book makes recommendations to improve aspects of programs - postdoctoral period of service, title and role, career development, compensation and benefits, and mentoring. Current data on demographics, career aspirations, and career outcomes for postdocs are limited. This report makes the case for better data collection by research institution and data sharing. A larger goal of this study is not only to propose ways to make the postdoctoral system better for the postdoctoral researchers themselves but also to better understand the role that postdoctoral training plays in the research enterprise. It is also to ask whether there are alternative ways to satisfy some of the research and career development needs of postdoctoral researchers that are now being met with several years of advanced training. Postdoctoral researchers are the future of the research enterprise. The discussion and recommendations of The Postdoctoral Experience Revisited will stimulate action toward clarifying the role of postdoctoral researchers and improving their status and experience.

Trends in the Innovation Ecosystem: Can Past Successes Help Inform Future Strategies? Summary of Two Workshops - National Academy of Sciences; National Academy of Engineering; Institute of Medicine
Innovation has been a major engine of American economic and societal progress. It has increased per capita income more than sevenfold since the 19th century, has added three decades to the average lifespan, has revolutionized the way we communicate and share information, and has made the United States the strongest military power in the world. Without its historical leadership in innovation, the United States would be a very different country than it is today. Trends in the Innovation Ecosystem is the summary of two workshops hosted by the Committee on Science, Engineering, and Public Policy (COSEPUP) of the National Academy of Sciences, National Academy of Engineering, and Institute of Medicine in February and May, 2013. Experts from industry, academia, and finance met to discuss the challenges involved in innovation pathways. Both workshops focused on the interactions between research universities and industry and the concept of innovation as a \

Examining Core Elements of International Research Collaboration: Summary of a Workshop - National Academy of Sciences; National Academy of Engineering; Institute of Medicine (The National Academies Press, 2011)
The globalization of science, engineering, and medical research is proceeding rapidly. The globalization of research has important implications for the U.S. research enterprise, for the U.S. government agencies, academic institutions, and companies that support and perform research, and for the world at large. As science and technology capabilities grow around the world, U.S.-based organizations are finding that international collaborations and partnerships provide unique opportunities to enhance research and training. At the same time, significant obstacles exist to smooth collaboration across national borders. Enhancing international collaboration requires recognition of differences in culture, legitimate national security needs, and critical needs in education and training. In response to these trends, the Government-University-Industry Research Roundtable (GUIRR) launched a Working Group on International Research Collaborations (I-Group) in 2008, following its meeting on New Partnerships on a Global Platform that June. As part of I-Group's continuing effort, a workshop on Examining Core Elements of International Research Collaboration was held July 26-27, 2010 in Washington, DC. One primary goal of the workshop is to better understand the risks involved in international research collaboration for organizations and individual participants, and the mechanisms that can be used to manage those risks. Issues to be addressed in the workshop include the following: (1) Cultural Differences and Nuances; (2) Legal Issues and Agreements; (3) Differences in Ethical Standards; (4) Research Integrity and the Responsible Conduct of Research; (5) Intellectual Property; (6) Risk Management; (7) Export Controls; and (8) Strategies for Developing Meaningful International Collaborations. The goal for the workshop and the summary, Examining Core Elements of International Research Collaboration, is to serve as an information resource for participants and others interested in international research collaborations. It will also aid I-Group in setting its future goals and priorities.

Culture Matters: International Research Collaboration in a Changing World: Summary of a Workshop - National Academy of Sciences; National Academy of Engineering; Institute of Medicine
In an increasingly interconnected world, science and technology research often transects international boundaries and involves researchers from multiple nations. This paradigm provides both new opportunities and new challenges. As science and technology capabilities grow around the world, United States-based organizations are finding that international collaborations and partnerships provide unique opportunities to enhance research and training. At the same time, enhancing international collaboration requires recognition of differences in culture, legitimate national security needs, and critical needs in education and training. Culture Matters is the summary of a workshop convened by the Government-University-Industry Research Roundtable (GUIRR) in July 2013 to address how culture and cultural perception influence and impact the process by which research agreements are made and negotiated across international boundaries. In this workshop, \

The Arc of the Academic Research Career: Issues and Implications for U.S. Science and Engineering Leadership: Summary of a Workshop - National Academy of Sciences; National Academy of Engineering; Institute of Medicine (The National Academies Press, 2014)
America's research universities have undergone striking change in recent decades, as have many aspects of the society that surrounds them. This change has important implications for the heart of every university: the faculty. To sustain their high level of intellectual excellence and their success in preparing young people for the various roles they will play in society, universities need to be aware of how evolving conditions affect their ability to attract the most qualified people and to maximize their effectiveness as teachers and researchers. Gender roles, family life, the demographic makeup of the nation and the faculty, and the economic stability of higher education all have shifted dramatically over the past generation. In addition, strong current trends in technology, funding, and demographics suggest that change will continue and perhaps even accelerate in academe in the years to come. One central element of academic life has remained essentially unchanged for generations, however: the formal structure of the professorial career. Developed in the mid-nineteenth and early twentieth centuries to suit circumstances quite different from today's, and based on traditions going back even earlier, this customary career path is now a source of strain for both the individuals pursuing it and the institutions where they work. The Arc of the Academic Research Career is the summary of a workshop convened by The Committee on Science, Engineering, and Public Policy in September 2013 to examine major points of strain in academic research careers from the point of view of both the faculty members and the institutions. National experts from a variety of disciplines and institutions discussed practices and strategies already in use on various campuses and identified issues as yet not effectively addressed. This workshop summary addresses the challenges universities face, from nurturing the talent of future faculty members to managing their progress through all the stages of their careers to finding the best use of their skills as their work winds down.

The Experimental Program to Stimulate Competitive Research - National Academy of Sciences; National Academy of Engineering; Institute of Medicine (The National Academies Press, 2013)
The primary federal program designed to ensure that all states are capable of participating the nation's research enterprise fall under the general rubric of the Experimental Program to Stimulate Competitive Research (EPSCOR). The National Science Foundation (NSF), Department of Energy, Department of Agriculture, and National Aeronautics and Space Administration have active EPSCOR programs. Since its inaugural year in 1979, the EPSCOR program has grown from funding programs in five states to awarding funding to 31 states in 2012. The Experimental Program to Stimulate Competitive Research assesses the effectiveness of EPSCOR and similar federal agency programs in improving national research capabilities, promoting an equitable distribution of research funding, and integrating their efforts with other initiatives designed to strengthen the nation's research capacity. This report also looks at the effectiveness of EPSCOR states in using awards to develop science engineering research and education, as well a science and engineering infrastructure within their state. The Experimental Program to Stimulate Competitive Research makes recommendations for improvement for each agency to create a more focused program with greater impact.

Sharing Clinical Research Data: Workshop Summary - Institute of Medicine
Pharmaceutical companies, academic researchers, and government agencies such as the Food and Drug Administration and the National Institutes of Health all possess large quantities of clinical research data. If these data were shared more widely within and across sectors, the resulting research advances derived from data pooling and analysis could improve public health, enhance patient safety, and spur drug development. Data sharing can also increase public trust in clinical trials and conclusions derived from them by lending transparency to the clinical research process. Much of this information, however, is never shared. Retention of clinical research data by investigators and within organizations may represent lost opportunities in biomedical research. Despite the potential benefits that could be accrued from pooling and analysis of shared data, barriers to data sharing faced by researchers in industry include concerns about data mining, erroneous secondary analyses of data, and unwarranted litigation, as well as a desire to protect confidential commercial information. Academic partners face significant cultural barriers to sharing data and participating in longer term collaborative efforts that stem from a desire to protect intellectual autonomy and a career advancement system built on priority of publication and citation requirements. Some barriers, like the need to protect patient privacy, pre- sent challenges for both sectors. Looking ahead, there are also a number of technical challenges to be faced in analyzing potentially large and heterogeneous datasets. This public workshop focused on strategies to facilitate sharing of clinical research data in order to advance scientific knowledge and public health. While the workshop focused on sharing of data from preplanned interventional studies of human subjects, models and projects involving sharing of other clinical data types were considered to the extent that they provided lessons learned and best practices. The workshop objectives were to examine the benefits of sharing of clinical research data from all sectors and among these sectors, including, for example: benefits to the research and development enterprise and benefits to the analysis of safety and efficacy. Sharing Clinical Research Data: Workshop Summary identifies barriers and challenges to sharing clinical research data, explores strategies to address these barriers and challenges, including identifying priority actions and \

Integrity in Scientific Research: Creating an Environment That Promotes Responsible Conduct - Institute of Medicine; National Research Council
\

Science and Technology for America's Progress: Ensuring the Best Presidential Appointments in the New Administration - National Academy of Sciences; National Academy of Engineering; Institute of Medicine (The National Academies Press, 2008)
The new Obama administration and the 110th Congress elected in November 2008 will face immediate challenges. Events will not permit a leisurely leadership transition. The prompt appointment of a Presidential science adviser and the nomination of top officials in the new administration with the knowledge and experience to address complex problems will be essential. The concerns of the nation regarding jobs and economic growth, health care, national security, energy, and the environment demand informed action. Each of these concerns-from national security, economic development, health care, and the environment, to education, energy, and natural resources-is touched in essential ways by the nation's science and technology enterprise. This is the fourth in a series of books from the National Academies on the presidential appointment process, each delivered during a presidential election year with the goal of providing recommendations to the President-elect about appointing his senior science and technology leadership and pursuing sustained improvements in the appointments process.

Observations on the President's Fiscal Year 2003 Federal Science and Technology Budget - National Academy of Sciences; National Academy of Engineering; Institute of Medicine (The National Academies Press, 2002)
Fifth in a series of annual reports, this study provides observations on the Administration2019s FY 2003 budget proposal for federal science and technology (FS&T) programs. The first section of the report outlines the development during the 1990s of national goals for science and technology (S&T), re-iterating the importance of U.S. leadership in these fields. It also comments on development of approach to tabulating and analyzing the federal S&T investment. The second section of the report summarizes the President2019s FY 2003 budget proposal, including proposals for spending on research for countering terrorism. The third section provides observations on the President2019s proposal, noting differences in funding trends by agency and outlining an approach to FS&T budgeting that focuses on both priority-driven and discovery-oriented research. The final section provides recommendations for ensuring that federally-funded S&T programs provide high-quality research outcomes that are relevant to agency missions and provide the U.S. with global leadership in S&T.

Information Sharing and Collaboration: Applications to Integrated Biosurveillance: Workshop Summary - Institute of Medicine (The National Academies Press, 2012)
After the September 11, 2001, terrorist attacks and subsequent anthrax mailings, the U.S. government prioritized a biosurveillance strategy aimed at detecting, monitoring, and characterizing national security health threats in human and animal populations, food, water, agriculture, and the environment. However, gaps and challenges in biosurveillance efforts and integration of biosurveillance activities remain. September 8-9, 2011, the IOM held a workshop to explore the information-sharing and collaboration processes needed for the nation's integrated biosurveillance strategy.

Venture Philanthropy Strategies to Support Translational Research: Workshop Summary - Institute of Medicine
Many voluntary health organizations fund translational research. An increasing number of these organizations are looking at venture philanthropy as a critical way to advance their missions of helping patients and working to cure disease. A wide range of participants gathered on October 3, 2008 at the Beckman Center of the National Academies of Science for a workshop titled \

Ensuring the Integrity, Accessibility, and Stewardship of Research Data in the Digital Age - National Academy of Sciences; National Academy of Engineering; Institute of Medicine (The National Academies Press, 2009)
As digital technologies are expanding the power and reach of research, they are also raising complex issues. These include complications in ensuring the validity of research data; standards that do not keep pace with the high rate of innovation; restrictions on data sharing that reduce the ability of researchers to verify results and build on previous research; and huge increases in the amount of data being generated, creating severe challenges in preserving that data for long-term use. Ensuring the Integrity, Accessibility, and Stewardship of Research Data in the Digital Age examines the consequences of the changes affecting research data with respect to three issues - integrity, accessibility, and stewardship-and finds a need for a new approach to the design and the management of research projects. The report recommends that all researchers receive appropriate training in the management of research data, and calls on researchers to make all research data, methods, and other information underlying results publicly accessible in a timely manner. The book also sees the stewardship of research data as a critical long-term task for the research enterprise and its stakeholders. Individual researchers, research institutions, research sponsors, professional societies, and journals involved in scientific, engineering, and medical research will find this book an essential guide to the principles affecting research data in the digital age.

Rising Above the Gathering Storm Two Years Later: Accelerating Progress Toward a Brighter Economic Future: Summary of a Convocation - National Academy of Sciences; National Academy of Engineering; Institute of Medicine (The National Academies Press, 2009)
Rising Above the Gathering Storm Two Years Later: Accelerating Progress Toward a Brighter Economic Future summarizes a convocation held in April 2008 to commemorate the release of the original Gathering Storm report. The convocation featured participation by Members of Congress, Cabinet Secretaries, leaders from industry and academia, and other experts. The discussions reviewed progress made thus far in implementing the Gathering Storm recommendations to strengthen K-12 education in math and science, research, higher education, and the environment for innovation. Participants also noted that much additional work is needed to ensure that America remains a leader in science and engineering in the long term.

Rising Above the Gathering Storm, Revisited: Rapidly Approaching Category 5 - National Academy of Sciences; National Academy of Engineering; Institute of Medicine
In the face of so many daunting near-term challenges, U.S. government and industry are letting the crucial strategic issues of U.S. competitiveness slip below the surface. Five years ago, the National Academies prepared Rising Above the Gathering Storm, a book that cautioned: \

Rising Above the Gathering Storm, Revisited: Rapidly Approaching Category 5: Condensed Version - 2005 "Rising Above the Gathering Storm" Committee (The National Academies Press, 2011)
In 2005 the National Academies released Rising Above the Gathering Storm, a book focused on the ability of all Americans to compete for quality jobs in the evolving global economy. Rising Above the Gathering Storm concluded that a primary driver of the future economy and concomitant creation of jobs in the 21st century will be innovation, largely derived from advances in science and engineering. It proposed four overarching recommendations, underpinned by 20 specific implementing actions. The America COMPETES Act approved many of the recommendations set forth in Rising Above the Gathering Storm. In 2010, the National Academies released Rising Above the Gathering Storm, Revisited, an updated volume that outlines the work of the government and the private sector in the past five years. This volume also presents a series of thought-provoking factoids about the state of science and innovation in America. It asserts that the 20 actions previously endorsed should be fully implemented. This report is a condensed version of Rising Above the Gathering Storm, Revisited.